2007
DOI: 10.3200/jach.56.2.137-146
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use, Abuse, and Dependence Among Students at a Southeastern Regional University

Abstract: Mental health and student affairs professionals should be alert to the problems associated with Internet overuse, especially as computers become an integral part of college life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 4 publications
10
75
1
6
Order By: Relevance
“…A recent random telephone survey of the general U.S. population reported an estimate of .3-.7% (1). A study of Southern U.S. university students found that about a quarter met criteria for Internet dependence (20).…”
Section: Diagnosis and Prevalencementioning
confidence: 99%
“…A recent random telephone survey of the general U.S. population reported an estimate of .3-.7% (1). A study of Southern U.S. university students found that about a quarter met criteria for Internet dependence (20).…”
Section: Diagnosis and Prevalencementioning
confidence: 99%
“…but internet addicts are using it mainly for chat rooms, social media sites, computer games, cartoons and films. Moreover, these internet addicts prefer to use it while alone, (Sunwoo, 2002;Fortson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Test results also showed, by using the t-test, that there was no statistically significant difference between the genders in terms of Internet addiction. In a study by Fortson et al conducted on students at the university of Virginia, it was determined that there was no difference between girls and boys when it came to the average usage of the Internet (12 was noted between the two genders (13). Such differences between males and females, which should be further investigated, may be due to the differences in the amount of time spent online.…”
Section: Discussionmentioning
confidence: 94%